The Effect of Balance Training on Ankle Sprains in Badminton Players - Sumartiningsih, Sri (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2021)
Ankle sprains are common injuries in various sports. It has happened 54- 66.9% occur in badminton players. This study design used review articles study. A literature search was conducted systematically using ACSM, AJSM, BJSM, OJSM, and human sport and exercise databases to retrieve articles published until December 2013. Controlled trials and controlled laboratory studies comparing different strategies to promote early recovery of ankle sprain were included. There are limited studies on the balance training program and ankle sprain. Five control and treatment study were reviewed. The study reported that balance training programs significantly reduce ankle sprains. The Balance training program can be applied to reduce the risk of ankle sprains in badminton players.